Contribution to the Chinese subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae; Rhaphidophorinae): New additions to the genera Eurhaphidophora and Stonychophora - Bian, Xun; Shi, Fuming (Zootaxa, 2016)
A key to the genera of Rhaphidophorinae is present. One new species of Eurhaphidophora, E. truncata Bian & Shi sp. nov., and the female sex of E. visibilis Gorochov, 2010 are described from China. Meanwhile, Stonychophora is recorded for the first time in the Chinese fauna and a new species viz., Stonychophora hainanensis, is described from Hainan. The voucher material is deposited in the Museum of Hebei University.